2020
DOI: 10.1016/j.cad.2020.102827
|View full text |Cite
|
Sign up to set email alerts
|

Level-set Based Design of Wang Tiles for Modelling Complex Microstructures

Abstract: Microstructural geometry plays a critical role in the response of heterogeneous materials. Consequently, methods for generating microstructural samples are increasingly crucial to advanced numerical analyses. We extend Sonon et al.'s unified framework, developed originally for generating particulate and foam-like microstructural geometries of Periodic Unit Cells, to non-periodic microstructural representations based on the formalism of Wang tiles. This formalism has been recently proposed in order to generaliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Visually appealing, nonperiodic yet compressed arrangements have impelled the adaptation of Wang tiles in computer graphics to generate naturally-looking textures [41,42] and Poisson disk distributions [41,43]. Sharing objectives, these applications have inspired the use of Wang tiles in modeling materials microstructures, both for geometrical representation [44,45,46] and calculations [47,48,49,50]. Because the cardinality of the Wang tileset balances the computation efficiency of the PUC with precise (micro-)structural description, Wang tilings also appear to be useful in securing automatic connectivity in the topology optimization of modular truss structures [8].…”
Section: Wang Tilingsmentioning
confidence: 99%
“…Visually appealing, nonperiodic yet compressed arrangements have impelled the adaptation of Wang tiles in computer graphics to generate naturally-looking textures [41,42] and Poisson disk distributions [41,43]. Sharing objectives, these applications have inspired the use of Wang tiles in modeling materials microstructures, both for geometrical representation [44,45,46] and calculations [47,48,49,50]. Because the cardinality of the Wang tileset balances the computation efficiency of the PUC with precise (micro-)structural description, Wang tilings also appear to be useful in securing automatic connectivity in the topology optimization of modular truss structures [8].…”
Section: Wang Tilingsmentioning
confidence: 99%
“…In the series of our previous works [33,34,35], we have introduced the framework of Wang tiles as a suitable extension of the (Statistically Equivalent) Periodic Unit Cell methodology for modelling microstructural geometry of random heterogeneous materials. We have shown that replacing the unit cell based representation with a set of domains-Wang tiles-with predefined mutual compatibility enables an efficient generation of stochastic microstructural realizations that feature suppressed periodicity artefacts [33,34,35] Even though the spurious periodicity is significantly reduced in the generated microstructural samples, they are still composed of only a handful of tiles. The Wang tile concept thus provides a finite-size discrete parametrization space of all realizations.…”
Section: Our Contributionmentioning
confidence: 99%
“…So far, three design strategies have been proposed: an optimization approach to minimize a discrepancy between spatial statistics of the reference specimen and generated assemblies [33], a sample-based strategy [34], and a levelset based framework for particulate and foam-like microstructures [35]. However, most of the methods developed for generating PUC can in principle be modified to adopt the generalized periodicity constraints of Wang tiles.…”
Section: Wang Tiles As Microstructural Rommentioning
confidence: 99%
See 2 more Smart Citations